Métodos de evaluación de programas nutricionales de gran escala en América Latina: una revisión integrativa (2015)
ABSTRACT: The evaluation of social programs is a field of knowledge in consolidation, involving different disciplines. It uses the social research tools but have particular goals that distinguish from it. Objective: This study aimed to identify methodological designs currently used to evaluate the nutritional programs in Latin America, including the types of studies conducted on the assessments, the dimensions assessed and indicators used. Methods: An integrative revision was carried out. Several electronic databases were consulted; likewise web pages of international agencies and institutions were searched by using a manual process. Results: 92 evaluations of 40 programs were analyzed, we found that in most cases no explicit methodological design was used in the evaluation. In those cases where if do, mostly showed three designs: consistency and results, multidimensional model and triangulation of methods. The dimensions mostly assessed are the program ́s impact and outcomes and to a lesser extent its structure and process. The types of study used to measure the impact of nutritional programs remain quantitative in nature especially quasi-experimental, however there is an effort made by some scholars by using qualitative tools that account for the perceptions of the actors involved. Conclusions. We found an interest in some institutions for carrying out assessments based on new paradigms and exploring combination of methods, objectives and indicators.